2021
DOI: 10.1016/j.sjbs.2021.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Relevance between COVID-19 and host genetics of immune response

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) was caused by the newly emerged corona virus (2019-nCoV alias SARS-CoV-2) that resembles the severe acute respiratory syndrome virus (SARS-CoV). SARS-CoV-2, which was first identified in Wuhan (China) has spread globally, resulting in a high mortality worldwide reaching ∼4 million deaths to date. As of first week of July 2021, ∼181 million cases of COVID-19 have been reported. SARS-CoV-2 infection is mediated by the binding of virus spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…The ACE-2 gene acts as a receptor on the surface of cells, and it is through this interaction that the SARS-CoV-2 virus enters in human cells [20]. The relationship between COVID-19 susceptibility and severity has been of great interest [49][50][51], and previous studies have suggested that higher levels of ACE-2 expression may be associated with greater ease of viral entry and, thus, greater severity of COVID-19, and this may be the result of a complex interaction between multiple factors, including the host immune response [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The ACE-2 gene acts as a receptor on the surface of cells, and it is through this interaction that the SARS-CoV-2 virus enters in human cells [20]. The relationship between COVID-19 susceptibility and severity has been of great interest [49][50][51], and previous studies have suggested that higher levels of ACE-2 expression may be associated with greater ease of viral entry and, thus, greater severity of COVID-19, and this may be the result of a complex interaction between multiple factors, including the host immune response [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…87,88 Among the various HLA molecules, those of classes I and II are the most important, with the former inducing the cytotoxic action of CD8+ T cells by inducing programmed cell death of infected cells 89 and the latter characterized by their high specificity in binding and presenting antigens to CD4+ T cells (Figure 2). 90 The process of binding to antigens is mediated by interaction in the peptide-binding grooves of the complex proteins, followed by proteolysis of the epitopes and finally their presentation. 87 The extensive number of polymorphisms in HLA genes characterize a large variability in the immune response produced, making possible genotypes strong markers that impact susceptibility to viral infections.…”
Section: Hla-mediated Immune Response To Sars-cov-2mentioning
confidence: 99%
“…The ability to activate CD4+ T cells is restricted to antigen-presenting cells that are endocytosed and processed in lysosomes for presentation on MHC class II molecules, which can transduce signals required for B-cell activation. Moreover, MHC class II antigen presentation by B lymphocytes is a multistep process involving in the presentation of MHC II-peptide complexes to CD4+ T cells ( 44 47 ). Although the host’s innate immune system works against the virus particles in this process, a small number of viruses still escape, and the RNAs released by these viruses are captured and identified by toll-like receptors (TLRs).…”
Section: Pathogenesis Of Sars-cov-2 and Regulation Of Related Circrnasmentioning
confidence: 99%